Cow-Based Zero Budget Natural Agricultural Practises for Underprivileged Farmers - Pazhanisamy, Benaka Prasad SB (International Journal of Modern Agriculture, 2021)
The importance of eating nutritious and chemical-free foods is increasingly increasing. Consumers are willing to pay more for high-quality produce. To achieve economic empowerment, farmers must seize this entrepreneurial potential. In this context, one such attempt by a farmers' interest group was examined. In the paper, the formation as well as behaviour of the group, as well as the group dynamics of the group members, were investigated and discussed. Using the case study process, first-hand information was gathered through a well-planned interview programme, in-depth interviews with community participants, and the researcher's crucial findings. The Group Dynamics Index (GDI) was created to assess the dynamics of a group of people. This paper aims to reveal a better agricultural method for poor and marginal land owners in order to increase their profits. Farmers are being motivated to invest less and grow more under the zero-budget natural farming scheme. Jivamrut and Dashparniark, which are made from cow dung and urine, are used by farmers. This has resulted in improved soil beneficial micro and macro flora and fauna, as well as a 40 to 45 percent reduction in agricultural costs. Farmers make a lot of money as they go to the shop to sell their products. This has resurrected the conventional mixed-cropping method and reduced farmers' reliance on the demand for seeds and inputs.